ANALISIS PERAN INSPEKTORAT DAERAH ISTIMEWA YOGYAKARTA SEBAGAI AUDITOR INTERNAL PEMERINTAH DALAM MENYELESAIKAN SALAH SATU TEMUAN PADA UNIT PELAKSANA TEKNIS DAERAH ABC DAERAH ISTIMEWA YOGYAKARTA TAHUN 2017 - Ari Nugroho Cahyono (Master in Accounting Program, 2019)
ABSTRACT This research aimed at analyzing the auditing process carried out by Yogyakarta Special Region Inspectorate in solving a finding in ABC Yogyakarta. It was also to investigate the audit communication and efforts done by the ABC Regional Technical Implementation Unit (UPTD) in solving and avoiding the finding to re-occur. Yogyakarta Special Region Inspectorate is a governmental internal auditor assigned to monitor the accountability administration and the activities of Yogyakarta Special Region government to achieve good governance. The ABC UPTD is one of the investigation objects with the Inspectorate’s biggest finding in the Special Region of Yogyakarta on the UPTD level in 2017. This research was qualitative with the case study method. To collect data, interviews and document analyses were used. The results showed that the finding process started from the auditor’s inspection on the janitors not yet registered for the Social Security Administration Body for Employment (BPJS Ketenagakerjaan). The inspection results were confronted with the document review to raise the case into an audit finding. There were then four audit communications with the investigation object, namely findings, affirmation, delivery of the Report of Audit Findings (LHP), and monitoring. The ABC UPTD then examined the finding closely and followed the Inspectorate recommendations. To avoid the re-occurrence of the finding, the ABC UPTD conducted an evaluation and improved its internal monitoring. The research was limited to one finding of the Inspectorate’s LHP, so that it is expected that the results can be interpreted carefully. In addition, the research respondents were also limited. In fact, the research has not yet analyzed any different cases or objects that require different settlements by the Inspectorate.